Heavy metal pollution characteristics and potential ecological risk assessment of soils around three typical antimony mining areas and watersheds in China - Qi, Yanting; Wei, Xiangdong; Zhao, MengJie; Pan, Weisong; Jiang, Chao; Wu, Jinbiao; Li, WaiChin (Frontiers in Environmental Science, 2022)
China is the largest antimony resource globally. The mining and smelting of antimony will inevitably have a significant impact on the surrounding and downstream farmlands of the mining area, Therefore, it is necessary to understand the pollution characteristics of antimony and evaluate its potential environmental risks. In this paper, three typical antimony mining areas were used as research districts to analyze the contents of heavy metals in soils of the mining areas and watersheds. The single-factor pollution index method, Nemerow comprehensive pollution index method, geo-accumulation index method, and potential ecological risk index method were used to comprehensively evaluate the pollution status and ecological risk of heavy metals in soils around the mining areas. The soil around the Lengshuijiang tin mine was polluted by As, Cd, Zn, and Sb, it was a heavily polluted soil and at a high ecological risk level. The arable soil around the Nandan tea mountain antimony mine was polluted by As, Cd, Cu, Pb, Sb, and Zn, and it was a heavily polluted soil with very high ecological risk level. The soil around the Xunyang antimony mine was mainly polluted by Sb and it was a moderately polluted soil with moderate ecological risk level. The results revealed that the overall soil heavy metal levels in the Lengshuijiang mining area and the Nandan mining area were in a high-risk state, most likely due to the mining and smelting of metal ores and the weathering of mineralised rocks. showing a high-potential ecological risk in these mining areas. We expect to provide a scientific basis for the safe utilization of farmland and pollution control around the antimony mining areas and watersheds in China.